Intraspecific Diversity of Fission Yeast Mitochondrial Genomes - Tao, Yu-Tian (Genome Biol Evol, 2019)
The fission yeast Schizosaccharomyces pombe is an important model organism, but its natural diversity and evolutionary history remain under-studied. In particular, the population genomics of the S. pombe mitochondrial genome (mitogenome) has not been thoroughly investigated. Here, we assembled the complete circular-mapping mitogenomes of 192 S. pombe isolates de novo, and found that these mitogenomes belong to 69 nonidentical sequence types ranging from 17,618 to 26,910 bp in length. Using the assembled mitogenomes, we identified 20 errors in the reference mitogenome and discovered two previously unknown mitochondrial introns. Analyzing sequence diversity of these 69 types of mitogenomes revealed two highly distinct clades, with only three mitogenomes exhibiting signs of inter-clade recombination. This diversity pattern suggests that currently available S. pombe isolates descend from two long-separated ancestral lineages. This conclusion is corroborated by the diversity pattern of the recombination-repressed K-region located between donor mating-type loci mat2 and mat3 in the nuclear genome. We estimated that the two ancestral S. pombe lineages diverged about 31 million generations ago. These findings shed new light on the evolution of S. pombe and the data sets generated in this study will facilitate future research on genome evolution.